Khalil bin Ahmad al-Farahidi's Contribution to the Development of Arabic Language Science and its Implication in Learning in the Modern Era: English - Amru Saputra; Moh. Abdul Kholiq Hasan (Universitas Djuanda, 2025)
Khalil bin Ahmad al-Farahidi is one of the most influential figures in the development of classical Arabic linguistics. He is known to be the originator of al-'Ayn, the first dictionary of Arabic systematically organised based on phonetic and morphological principles, and the inventor of the science of 'Arūḍ which discusses the metrical structure of Arabic poetry. In addition, his contributions to the development of nahwu and the establishment of grammatical rules have provided a crucial foundation for Arabic linguistics. This study aims to examine in depth al-Farahidi's intellectual donation to Arabic linguistics and analyse its relevance in the context of Arabic language learning in the modern era. The approach used means historical literature review and conceptual analysis, tracing his works and thoughts and linking them using contemporary learning practices. The research states that the phonetic, morphological, and analytical systematic approaches developed by al-Farahidi are very relevant to be applied in the latest curriculum, especially in technology-based learning and contextual linguistics. His scholarly legacy not only has historical value, but is also functional in the development of today's Arabic language education discoveries.